2018
DOI: 10.1108/jfrc-01-2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

Perspective of corporate governance and ethical issues with profit sharing investment accounts in Islamic banks

Abstract: Purpose The purpose of this paper is to examine the practices of Islamic banks in managing the so-called profit sharing investment accounts (PSIA) which they offer as a Shari’ah-compliant alternative to interest-bearing deposit accounts using an unrestricted Mudarabah contract. In particular, the paper aims to examine the risk-return characteristics of such accounts and to compare these to the returns and risks of shareholders in the same banks. It is relevant that PSIA holders (unrestricted investment account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…Hence, IBs institute interest-free concepts and promote PLS products such as Mudarabah and Musharakah that direct the society towards socio-economic justice. However, Alhammadi et al (2018) suggest that the practice of IBs was unsuccessful in applying the principle of PLS, which indicates that IBs' principles exist more in literature and theory than in real practice. Thus, IBs should comprise Islamic ethical values to compete with conventional banks regarding profitability and efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, IBs institute interest-free concepts and promote PLS products such as Mudarabah and Musharakah that direct the society towards socio-economic justice. However, Alhammadi et al (2018) suggest that the practice of IBs was unsuccessful in applying the principle of PLS, which indicates that IBs' principles exist more in literature and theory than in real practice. Thus, IBs should comprise Islamic ethical values to compete with conventional banks regarding profitability and efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the first generation of scholars have prioritised Maqās id al-Sharī'ah fulfilments as a crucial objective to achieve social justice (Hassan and Aliyu 2018). As stated by Alhammadi et al (2018), Islam does not object to the profit motive as such but insists on equity and fairness. Islamic economics seeks to promote PLS on both sides of the balance sheet.…”
Section: The Discrepancy In Socio-economic Justicementioning
confidence: 99%
“…Ashbaugh-Skaife et al (2006) and Grassa (2016) showed that CEO duality negatively affects the firm's credit rating. On the other hand, Alhammadi et al (2018) showed that CEO duality affects the rate of returns between the two classes of stakeholders in Islamic banks. In the case of duality in any Islamic bank, the shareholders get a better return on their investment.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Displaced commercial risk occurs when the profit expectations of Islamic bank investment account holders are higher than actual returns (Toumi et al , 2019). This makes Islamic banks subject to withdrawal risk (Archer et al , 2010; Aysan et al , 2014; Alhammadi, 2016; Aysan et al , 2016; Alhammadi et al , 2018; Noor et al , 2019a) that may hamper their financial standing and subject them to systemic risk (Toumi et al , 2019). To ensure their competitiveness, Islamic banks bear losses when their expected pay off to investment account holders is lower than the market and retain a higher share of profits when their expected pay off to investment account holders is higher than the market (Alhammadi, 2016; Alhammadi et al , 2018; Noor et al , 2019a; Toumi et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is because Islamic banks do not have any obligation to pay returns to Unrestricted Investment Account Holders (UIAH) in the absence of profits, and in any case, may use reserves taken from prior-year UIAH profits to pay returns in years when profits are lacking. In the absence of governance rights, the only safeguard UIAH’s might have would be effective competition between Islamic banks for their funds together with transparency and market discipline, but the evidence suggests that these are insufficient.” (Alhammadi et al , 2018; p 16).…”
Section: Literature Reviewmentioning
confidence: 99%